2007
DOI: 10.1348/000709906x105328
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative philosophical enquiry for school children: Cognitive effects at 10–12 years

Abstract: Philosophical enquiry involving interactive dialogue led not only to significant gains in measured verbal cognitive ability but also generalization to non-verbal and quantitative reasoning ability, consistent across schools and largely irrespective of pupil gender and ability. The effect sizes from this large-scale field trial in one local authority exceeded those reported in the literature. Implications for theory building, replicability and sustainability are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 19 publications
3
48
1
12
Order By: Relevance
“…Emphasis on “thinking” and “drawing conclusions” are also key in classroom interventions such as Cognitive Acceleration through Science Education (CASE) and Philosophy for Children (P4C), in which inquiry‐orientated teaching and learning is the focus. Both programs have reported large positive effects on students’ levels of thinking (Adey & Shayer, ; Oliver, Venville, & Adey, ; Topping & Trickey, ) and gains in students’ self‐esteem (Trickey & Topping, ). That some approaches to inquiry are demonstrably successful in improving students’ achievement in science resonates with CASE and P4C, in that students are expected to reflect, justify, and explain ideas, use evidence, and reason.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on “thinking” and “drawing conclusions” are also key in classroom interventions such as Cognitive Acceleration through Science Education (CASE) and Philosophy for Children (P4C), in which inquiry‐orientated teaching and learning is the focus. Both programs have reported large positive effects on students’ levels of thinking (Adey & Shayer, ; Oliver, Venville, & Adey, ; Topping & Trickey, ) and gains in students’ self‐esteem (Trickey & Topping, ). That some approaches to inquiry are demonstrably successful in improving students’ achievement in science resonates with CASE and P4C, in that students are expected to reflect, justify, and explain ideas, use evidence, and reason.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of Hawthorne Effect in the experimental gains must be countenanced, but it seems unlikely this would endure over seven months. Measures of implementation integrity of the intervention were made, by video recording and analysis of classroom interactions, and these are reported elsewhere (Topping and Trickey, 2006a). Measures of cognitive outcomes were also made, and these are reported elsewhere (Topping and Trickey, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Using P4C, the authors investigated the effects of this approach to dialoguing on students' academic, social, and cognitive abilities with the Trickey and Topping (2006) finding significant positive socio-emotional effects while Topping and Trickey (2007a) reported that students recorded significant standardised gains in verbal and non-verbal reasoning ability that generalised to non-verbal and quantitative reasoning ability. Furthermore, these gains were maintained when Topping and Trickey (2007b) followed these students up two-years later after they had transferred to high school even though they had not received further instruction in P4C.…”
Section: Philosophy For Childrenmentioning
confidence: 99%